On removable sets of solutions of second-order elliptic and parabolic equations in nondivergent form - Gadjiev, T. S.; Mamedova, V. A. (Ukrains’kyi Matematychnyi Zhurnal, 2009)
We consider nondivergent elliptic and parabolic equations of the second order whose leading coefficients satisfy the uniform Lipschitz condition. We find a sufficient condition for the removability of a compact set with respect to these equations in the space of Hölder functions.